Optimization of IDLE Assets in Support of Improving the Efficiency of Local Government in Grobogan Regency - Adi Saputra, Dany; Allief Sudiro; Gayuh Eva Marliana; Athallah Azam Archiebald Amna; Muhammad Naufal Kautsar; Esa Wiji Kinasih; Hamidah, Afi Asyrofatul (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze the potential for optimizing the vacant land of the Grobogan Regency government as a strategic step to increase the efficiency of regional government and PAD. Field surveys, direct observation, and literature research on asset management are the methods used. The research results show that 86% of land assets have been managed productively, while 14% are still in a neglected condition and have not provided significant economic benefits. Reducing public awareness, lack of appeal to the public and lack of a good monitoring system are the main problems in managing idle assets. To overcome this problem, accelerated asset re-inventory, use of asset management technology, and outreach to residents and village heads are needed. In short, optimizing vacant land using modern technology and a participatory approach can increase PAD and encourage sustainable local economic development.